The Otago Exercise Program's effect on fall prevention: a systematic review and meta-analysis - Chenyu Wang; Sung Min Kim; Sung Min Kim; Sung Min Kim (Frontiers in Public Health)
ObjectivesThis study aims to compare the effectiveness of the Otago Exercise Program (OEP) in fall prevention between generally healthy older adults and those with compromised health conditions, assessing which group benefits more from the intervention.DesignThis meta-analysis evaluated the effectiveness of the OEP in fall prevention among general older adults and older adults with compromised health, including individuals at high risk of falls, cognitive impairment, musculoskeletal disorders, or frailty syndrome.MethodsA comprehensive search was conducted in Web of Science, PubMed, Scopus, Cochrane Library, and Embase, following strict eligibility criteria. Data extraction, risk of bias assessment, and meta-analysis were conducted to evaluate the effectiveness of the intervention.ResultsFifteen studies with 1,278 participants were included. The OEP significantly improved balance (WMD = 0.15, 95% CI [–0.05, 0.35]), gait (WMD = 0.49, 95% CI [0.18, 0.80]), and lower limb strength (WMD = 0.84, 95% CI [0.61, 1.07]) in general older adults. The effects were more pronounced in older adults with compromised health, particularly in gait, particularly in gait (WMD = 0.92, 95% CI [0.13, 1.72]) and lower limb strength (WMD = 2.24, 95% CI [1.04, 3.45]). However, the OEP did not significantly improve physical function or upper limb strength in either group.ConclusionThe OEP effectively improves balance, gait, and lower limb strength, especially in older adults with compromised health. However, it does not significantly impact physical function or upper limb strength. This study has limitations, including potential bias, study heterogeneity, and variations in interventions, which may affect result reliability. A cautious interpretation is needed, and future research should focus on analyzing diverse populations and ensuring adequately sized samples to enhance the reliability of the findings.Systematic review registrationPROSPERO (CRD42024549302), https://www.crd.york.ac.uk/PROSPERO/view/CRD42024549302.